Genetic modification of heterochromatic association and nuclear organization in Drosophila. - Csink, A.K.; Henikoff, S. (Nature, 1996)
Heterochromatin is the highly compact, usually pericentromeric, region of eukaryotic chromosomes. Unlike the more gene-rich euchromatin, heterochromatin remains condensed during interphase, when it is sequestered to the periphery of the nucleus. Here we show, by using fluorescent in situ hybridization to interphase diploid nuclei of Drosophila, that the insertion of heterochromatin into a euchromatic gene, which results in position-effect variegation (PEV), also causes the aberrant association of the gene and its homologous copy with heterochromatin. In correlation with the gene's mutant variegating phenotype, the cytological association of the heterochromatic region is affected by chromosomal distance from heterochromatin and by genic modifiers of PEV. Proteins that are thought to be involved in the formation of heterochromatin can therefore influence the interphase nuclear position of a chromosomal region. This suggests that heterochromatin and proteins involved in its formation provide a structural framework for the interphase nucleus.